Third Five-Year Plan Programme for 1961-62 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1961)
The Third Five-Year Plan of Andhra Pradesh was published in February, 1960— three months before the Plan was to commence its operation. The State Plan is a part of the National Plan and aims at fulfilling the targets assigned to the State under the various activities. The Prime Minister while speaking on the Third Five-Year Plans presented before the Parliament described it as a supreme challenge and yet no more than a minimum that must be assured as part of a larger 15-Year Programme of development that is intended to carry the economy into a state of self-generating growth. He said that the Plan called for national unity, discipline, sacrifice and the dedicated effort of every citizen in order to ensure its speedy and efficient implementation.
Planning and Local Administration Department, Government of Andhra Pradesh